In Search for the Meaning of Illness: Content of Narrative Discourse Is Related to Cognitive Deficits in Stroke Patients - Egbert, Anna R.; Pluta, Agnieszka; Powęska, Joanna; Łojek, Emilia (Frontiers in Psychology, 2021)
Stroke survivors undergo a thorough cognitive diagnosis that often involves administration of multiple standardized tests. However, patient’s narrative discourse can provide clinicians with additional knowledge on patient’s subjective experience of illness, attitude toward current situation, and motivation for treatment. We evaluated the methods of analysing thematic content and story types in relationship to cognitive impairment in stroke survivors with no aphasia (including 9 left hemisphere damage – LHD patients, and 16 right hemisphere damage – RHD patients). Cognitive impairment was evaluated in comparison to a group of 25 patients with orthopaedic injury not involving the brain. Our findings primarily show that higher elaboration on own cognitive problems, physical ailments or coping strategies in LHD patients and cognitive problems, emotional issues and circumstances of illness onset in RHD patients is related to deficits in executive functions and retrieval of information from memory. Furthermore, RHD patients who use more chaos story type show lower executive functioning. However, these results did not survive the significance threshold of p<0.05 after Bonferroni adjustment for multiple comparisons. In conclusion, this study provides preliminary evidence that stroke survivor’s narrative can constitute an additional source of clinically-relevant information regarding patient’s experience of illness and attitude toward recovery. This knowledge can aid clinicians and nurses in everyday interactions with the patients and support individualized strategy to treatment. Still, the current results need be confirmed with future studies in a larger cohort of stroke patients.